2017
DOI: 10.1007/978-3-319-54528-8_17-1
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical Potential of Apiaceae

Abstract: Apiaceae family is large, with over 3.000 species worldwide cultivated for many purposes. Some plants in this family such as carrots, parsley, parsnip and celery are common vegetable crops, while other members like anise, caraway, coriander, cumin, fennel, lovage, angelica and dill are famous for their medicinal and aromatic properties. Usage of these plants is very popular in everyday diet because of their documented health benefits. Apiaceae are a very important source of phytochemicalschemicals with biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 194 publications
(182 reference statements)
0
28
0
Order By: Relevance
“…Table (1) showed that the genotype "Gewone Dai 3 Rial 10" produced the highest yield of fresh leaves (as a total of three cuttings) in the two successive seasons (30.4 and 31.4 ton/fed) followed by Moskrul 2 Petra (21.4 and 20.1 ton/fed). While, Bravour (15.7 and 15.0 ton/fed) and Moskrul 2 KRA USA (14.9…”
Section: Total Yield Of Fresh Leaves (Ton/fed)mentioning
confidence: 99%
See 1 more Smart Citation
“…Table (1) showed that the genotype "Gewone Dai 3 Rial 10" produced the highest yield of fresh leaves (as a total of three cuttings) in the two successive seasons (30.4 and 31.4 ton/fed) followed by Moskrul 2 Petra (21.4 and 20.1 ton/fed). While, Bravour (15.7 and 15.0 ton/fed) and Moskrul 2 KRA USA (14.9…”
Section: Total Yield Of Fresh Leaves (Ton/fed)mentioning
confidence: 99%
“…Because of their well-documented health benefits, the usage of these plants is very widespread in everyday diet. Apiaceae is a very essential source of phytoconstituents (phenolic compounds, polyacetylenes, terpenoids,…etc) with various pharmacological activities [1]. One of these plants is parsley (Petroselinum crispum Mill.).…”
Section: Introductionmentioning
confidence: 99%
“…This is the case of Smyrnium olusatrum (commonly known as Alexanders), whose flavor is intermediate between celery and parsley and was greatly appreciated by Roman and medieval cuisines but has been progressively replaced by celery [ 9 ]. For a comprehensive review of the nutraceutical properties of the main Apiaceae species, see [ 22 ]. Some Apiaceae find application in the beverage industry, where they are used mainly as flavoring (e.g., Pimpinella anisum and Angelica archangelica , respectively employed for the preparation of Greek ouzo and Italian vermouth).…”
Section: General Introductionmentioning
confidence: 99%
“…Moreover, EOs exhibit anti-inflammatory effects, thus supporting lesion healing and alleviating symptoms related to dermatophytosis [14,15]. Apiaceae (Umbelliferae) family comprises 446 genera of 3540 herbaceous species distributed worldwide, many of them used in the food, pharmaceutical, and cosmetic industries [25,26]. A characteristic feature of Apiaceae members is the presence of volatile compounds which are found both in aerial parts and the underground systems of plants [27].…”
Section: Introductionmentioning
confidence: 99%